Sources of dissolved iron to oxygen minimum zone waters on the Senegalese continental margin in the tropical North Atlantic Ocean: Insights from iron isotopes. (1st September 2018) - Klar, J.K.; Schlosser, C.; Milton, J.A.; Woodward, E.M.S.; Lacan, F.; Parkinson, I.J.; Achterberg, E.P.; James, R.H.
Abstract: Oxygen minimum zones (OMZs) cover extensive areas of eastern boundary ocean regions and play an important role in the cycling of the essential micronutrient iron (Fe). The isotopic composition of dissolved Fe (dFe) in shelf and slope waters on the Senegalese margin was determined to investigate the processes leading to enhanced dFe concentrations (up to 2 nM) in this tropical North Atlantic OMZ. On the shelf, the δ 56 Fe value of dFe (relative to the reference material IRMM-014) was as low as −0.33‰, which can be attributed to input of dFe from both reductive and nonreductive dissolution of sediments. Benthic inputs of dFe are subsequently upwelled to surface waters and recycled in the water column by biological uptake and remineralisation processes. Remineralised dFe is characterised by relatively high δ 56 Fe values (up to +0.41‰), and the contribution of remineralised Fe to the total dFe pool increases with distance from the shelf. Remineralisation plays an important role in the redistribution of dFe that is mainly supplied by benthic and atmospheric inputs, although dust inputs, estimated from dissolved aluminium concentrations, were low at the time of our study (2–9 nmol dFe m −2 d −1 ). As OMZs are expected to expand as climate warms, our data provide important insights into Fe sources and Fe cycling in the tropical North Atlantic Ocean.